2010
DOI: 10.1016/j.envpol.2010.01.033
|View full text |Cite
|
Sign up to set email alerts
|

Mercury profiles in sediments of the Pearl River Estuary and the surrounding coastal area of South China

Abstract: The spatial and historical changes of Hg in sediment reflect the industrial development and urbanization of the region in south China. a r t i c l e i n f o a b s t r a c tThe spatial and temporal variations of mercury (Hg) in sediments of the Pearl River Estuary (PRE) and the surrounding coastal area (South China Sea) were studied. In surface sediments, the concentrations of Hg ranged from 1.5 to 201 ng/g, with an average of 54.4 ng/g, displaying a decreasing trend with the distance from the estuary to the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
34
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 82 publications
(44 citation statements)
references
References 28 publications
7
34
1
Order By: Relevance
“…This also suggests a significant influence of Hg discharges from nearby cities and coastal circulation currents. Compared to our previous survey on the PRE (Shi et al, 2010), the highest and average concentrations of Hg increased from 201 lg kg À1 to 398 lg kg À1 , and from 54.4 lg kg À1 to 166 lg kg À1 during the year 2002-2011, implying a significant increase of the anthropogenic emissions of Hg in the Pearl River Delta (PRD) region. Compared with published data on the background values of sedimentary Hg in the whole SCS (Zhang and Du, 2005), Hg levels in sediments of the PRE is relatively higher, indicating a strong impact of landbased anthropogenic Hg emissions.…”
contrasting
confidence: 62%
“…This also suggests a significant influence of Hg discharges from nearby cities and coastal circulation currents. Compared to our previous survey on the PRE (Shi et al, 2010), the highest and average concentrations of Hg increased from 201 lg kg À1 to 398 lg kg À1 , and from 54.4 lg kg À1 to 166 lg kg À1 during the year 2002-2011, implying a significant increase of the anthropogenic emissions of Hg in the Pearl River Delta (PRD) region. Compared with published data on the background values of sedimentary Hg in the whole SCS (Zhang and Du, 2005), Hg levels in sediments of the PRE is relatively higher, indicating a strong impact of landbased anthropogenic Hg emissions.…”
contrasting
confidence: 62%
“…However, there have been little available update data since the survey. Our recent studies in Pearl River Delta, one of the most industrialized and urbanized region in China, has shown that the concentrations of Hg in the sediments increased with the economic development in the last three decades (Shi et al , 2010. Studies also found high concentrations of Hg in the air and soil of some cities (Fang et al 2004;Feng et al 2003;Zhang et al 2004;Zhang and Wong 2007).…”
Section: Introductionmentioning
confidence: 98%
“…In the Pearl River estuary (Shi et al, 2010) Hg concentrations decrease on moving seawards along the estuary. In Venezuela, Ramos et al (2009) linked increases of Hg in coral skeletons to rainfall and runoff from industrial sites, while in the Caribbean, Guzman and Garcia (2002) found elevated Hg concentrations in various components of the reef environment, and related these to burning and mining activities with some evidence of long distance movement.…”
Section: Hg Concentrations Have Been Identified In Sediments In Variomentioning
confidence: 99%